(untitled) (Global Journal of Science Frontier Research, 2014)
Wetlands in Eastern Africa present an important and so far largely undocumented potential in terms of area and agricultural production. This potential is linked to the availability of water and the quality of soil resources. This study characterized representative wetlands and categorizes their diversity based on soil, hydrology and socio-economic attributes. A multidisciplinary regional assessment of more than 50 wetlands and over 150 wetland subunits was conducted in 2008 and 2009 in four regions of East Africa. The wetlands were located within the major landscape units comprising (i) the floodplain in the semi-arid highlands; (ii) floodplain in the sub-humid lowlands; (iii) inland valley swamps in the humid mid-hills; and (iv) inland valley swamps in the humid highlands. Based on multivariate statistical approaches of their biophysical and socio-economic attributes, the wetlands were categorized into five cluster groups which were further differentiated based on land use intensity, soil parameters and hydrology.